Skupni prevzem - Sotošek, Nina (Podjetje in delo, 2022)
The authors examine the institute of joint takeover or persons acting in concert, and its implementation in the Slovenian legal order. The institute was newly regulated in Slovenian law by the Takeovers Act (ZPre-1) in 2006 for the purpose of harmonisation with the Thirteenth EU Directive. The Directive's main purpose was to take the necessary measures at the EU level to protect minority shareholders in the event of taking control of their companies. The article also presents the reasons for the establishment of the institute, discusses issues related to its placement in the legislation, describes the legal presumptions and the legal consequences that arise with it. A comparative legal analysis of the regulation of the institute is discussed along with the relevant case law. The conclusions of the authors are given at the end.
Keywords: concentrations; gospodarske družbe; gospodarsko pravo; institut usklajenega delovanja; joint takeover; koncentriranje; persons acting in concert institute; prevzemi; skupni prevzemi; takeover; Thirteenth EU Directive; Trinajsta direktiva EU